Texts and traditions : religion in Shakespeare, 1592-1604 - Groves, Beatrice, 1978- (Oxford English monographs., 2007)
Explores Shakespeare's engagement with the religious culture of his time. Through readings of a number of plays - "Romeo and Juliet", "King John", "1 Henry IV", "Henry V", and "Measure for Measure", this work explains allusions to the Bible, the Church's liturgy, and to the mystery plays performed in England in Shakespeare's boyhood